Sphingosine-1-phosphate in Endothelial Cell Recellularization Improves Patency and Endothelialization of Decellularized Vascular Grafts In Vivo - Hsia, Kai (Int J Mol Sci, 2019)
Background: S1P has been shown to improve the endothelialization of decellularized vascular grafts in vitro. Here, we evaluated the potential of tissue-engineered vascular grafts (TEVGs) constructed by ECs and S1P on decellularized vascular scaffolds in a rat model. Methods: Rat aorta was decellularized mainly by 0.1% SDS and characterized by histology. Rat ECs, were seeded onto decellularized scaffolds, and the viability of the ECs was evaluated by biochemical assays. Then, we investigated the in vivo patency rate and endothelialization for five groups of decellularized vascular grafts (each n = 6) in a rat abdominal aorta model for 14 days. The five groups included (1) rat allogenic aorta (RAA); (2) decellularized RAA (DRAA); (3) DRAA with S1P (DRAA/S1P); (4) DRAA with EC recellularization (DRAA/EC); and (5) DRAA with S1P and EC recellularization (DRAA/EC/S1P). Results: In vitro, ECs were identified by the uptake of Dil-Ac-LDL. S1P enhanced the expression of syndecan-1 on ECs and supported the proliferation of ECs on decellularized vascular grafts. In vivo, RAA and DRAA/EC/S1P both had 100% patency without thrombus formation within 14 days. Better endothelialization, more wall structure maintenance and less inflammation were noted in the DRAA/EC/S1P group. In contrast, there was thrombus formation in the DRAA, DRAA/S1P and DRAA/EC groups. Conclusion: S1P could inhibit thrombus formation to improve the patency rate of EC-covered decellularized vascular grafts in vivo and may play an important role in the construction of TEVGs.